WAYS TO DEVELOP TECHNOLOGICAL KNOWLEDGE IN ELEMENTARY SCHOOL STUDENTS - Sanakulov Khamrakul Rizakulovich,; Sabirov Bakhtiyar Eshbaeviya,; Niyazmetova Nargiza Bakhramovna,; Magdieva Markhabo Erkinovna, (The Bioscan, 2025)
This article explores various strategies for enhancing the technological knowledge of elementary school students. Emphasizing the integration of STEM education, digital tools, and interactive learning methods, it aims to provide educators and curriculum developers with effective approaches to foster a tech-savvy generation. Keywords Technology Education, Elementary School, STEM, Digital Literacy, Educational Technology, Interactive Learning.